Diagnosis, Evaluation and Treatment of Pulmonary Arterial Hypertension in Children - Benjamin S. Frank; D. Dunbar Ivy (MDPI AG, 2018)
Pulmonary Hypertension (PH), the syndrome of elevated pressure in the pulmonary arteries, is associated with significant morbidity and mortality for affected children. PH is associated with a wide variety of potential underlying causes, including cardiac, pulmonary, hematologic and rheumatologic abnormalities. Regardless of the cause, for many patients the natural history of PH involves progressive elevation in pulmonary arterial resistance and pressure, right ventricular dysfunction, and eventually heart failure. In recent years, a number of pulmonary arterial hypertension (PAH)-targeted therapies have become available to reduce pulmonary artery pressure and improve outcome. A growing body of evidence in both the adult and pediatric literature demonstrates enhanced quality of life, functional status, and survival among treated patients. This review provides a description of select etiologies of PH seen in pediatrics and an update on the most recent data pertaining to evaluation and management of children with PH/PAH. The available evidence for specific classes of PAH-targeted therapies in pediatrics is additionally discussed.